LANGUAGE LEARNING STRATEGIES FOR EFL STUDENTS (Journal of Universal Science Research, 2023)
This article examines the dynamic landscape of language learning strategies for EFL students, elucidating how these strategies can be harnessed to surmount the hurdles faced in the journey towards proficiency